A one-pot synthesis-functionalization strategy for streamlined access to 2,5-disubstituted 1,3, 4-oxadiazoles from carboxylic acids - Matheau-Raven, D; Dixon, DJ (American Chemical Society, 2022)
A one-pot 1,3,4-oxadiazole synthesis-arylation strategy for accessing 2,5-disubstituted 1,3,4-oxadiazoles, from carboxylic acids, N-isocyaniminotriphenylphosphorane (NIITP), and aryl iodides, is reported. The reaction sequence, featuring a second stage copper-catalyzed 1,3,4-oxadiazole arylation, was found to tolerate (hetero)aryl, alkyl, and alkenyl carboxylic acids, and (hetero)aryl iodide coupling partners. The effectiveness of the two-stage strategy was exemplified by the late-stage functionalization of five carboxylic acid-containing APIs, and an extension to the synthesis of aminated 1,3,4-oxadiazoles using N-benzoyloxy amine coupling partners was also demonstrated.